Sexual Orientation and Gender Identity/Expression Related Peer Victimization in Adolescence: A Systematic Review of Associated Psychosocial and Health Outcomes - Collier, Kate L. (2013)
This article reviews research on psychosocial and health outcomes associated with peer victimization related to adolescent sexual orientation and gender identity or expression. Using four electronic databases and supplementary methods, we identified 39 relevant studies. These studies were published between 1995 and 2012 and conducted in 12 different countries. The studies were diverse in terms of their approaches to sampling participants, assessing participants’ sexual orientation, operationalizing peer victimization, and with regard to the psychosocial and health outcomes studied in relation to peer victimization. Despite the methodological diversity across studies, there is fairly strong evidence that peer victimization related to sexual orientation and gender identity or expression is associated with a diminished sense of school belonging and higher levels of depressive symptoms; findings regarding the relationship between peer victimization and suicidality have been more mixed. Peer victimization related to sexual orientation and gender identity or expression is also associated with disruptions in educational trajectories, traumatic stress, and alcohol and substance use. Recommendations for future research and interventions are discussed.